Parallel computational fluid dynamics : practice and theory : proceedings of the Parallel CFD 2001 Conference, Egmond aan Zee, the Netherlands (May 21-23, 2001) - Parallel CFD Conference (2001 : Egmond aan Zee, Netherlands); Wilders, P.; ScienceDirect eBooks (Amsterdam ; London : Elsevier, 2002)
ParCFD 2001, the thirteenth international conference on Parallel Computational Fluid Dynamics took place in Egmond aan Zee, the Netherlands, from May 21-23, 2001. The specialized, high-level ParCFD conferences are organized yearly on traveling locations all over the world. A strong back-up is given by the central organization located in the USA <SURL>http://www.parcfd.org</SURL>. These proceedings of ParCFD 2001 represent 70% of the oral lectures presented at the meeting. All published papers were subjected to a refereeing process, which resulted in a uniformly high quality. The papers cover not only the traditional areas of the ParCFD conferences, e.g. numerical schemes and algorithms, tools and environments, interdisciplinary topics, industrial applications, but, following local interests, also environmental and medical issues. These proceedings present an up-to-date overview of the state of the art in parallel computational fluid dynamics.
Cover -- Table of Contents -- Preface -- Acknowledgements -- Part 1: Opening paper: -- Chapter 1. An overview of ParCFD activities at Delft University of Technology -- Part 2: Invited and contributed papers: -- Chapter 2. Noise predictions for shear layers -- Chapter 3. Framework for parallel simulations in air pollution modeling with local refinements -- Chapter 4. Aerodynamic studies on a Beowulf cluster -- Chapter 5. Scalable numerical algorithms for efficient meta-computing of elliptic equations -- Chapter 6. Direct numerical simulation of jet noise -- Chapter 7. Migrating from a parallel single block to a parallel multiblock flow solver -- Chapter 8. Parallel multidimensional residual distribution solver for turbulent flow simulations -- Chapter 9. Parallel implementation of a line-implicit time-stepping algorithm -- Chapter 10. Parallel simulation of dense gas and liquid flows based on the quasi gas dynamic system -- Chapter 11. DLB 2.0 -- A distributed environment tool for supporting balanced execution of multiple parallel jobs on networked computers -- Chapter 12. Parallel computation of thrust reverser flows for subsonic transport aircraft -- Chapter 13. On a fast parallel solver for reaction-diffusion problems: application to air quality simulation -- Chapter 14. Algebraic coarse grid operators for domain decomposition based preconditioners -- Chapter 15. Efficient parallel simulation of disperse gas-particle flows on cluster computers -- Chapter 16. Large scale CFD data handling with off-the-shelf pc-clusters in a VR-based rhinological operation planning system -- Chapter 17. An optimised recoupling strategy for the parallel computation of turbomachinery flows with domain decomposition -- Chapter 18. Implementation of underexpanded jet problems on multiprocessor systems -- Chapter 19. Numerical simulation of scramjet engine inlets on a vector-parallel supercomputer -- Chapter 20. Parallel computation of multigrid method for overset grid -- Chapter 21. Parallel computing of transonic cascade flows using the Lattice-Boltzmann method -- Chapter 22. Parallel computation of multi-species flow using a Lattice-Boltzmann method -- Chapter 23. A weakly overlapping parallel domain decomposition preconditioner for the finite element solution of convection-dominated problems in three dimensions -- Chapter 24. Lattice-Boltzmann simulations of inter-phase momentum transfer in gas-solid flows -- Chapter 25. Parallel CFD simulations of multiphase systems: jet into a cylindrical bath and rotary drum on a rectangular bath -- Chapter 26. Zooming in on 3D magnetized plasmas with grid-adaptive simulations -- Chapter 27. Parallel calculations for transport equations in a fast neutron reactor -- Chapter 28. Parallel large scale computations for aerodynamic aircraft design with the German CFD system MEGAFLOW -- Chapter 29. Towards stability analysis of three-dimensional ocean circulations on the TERAS -- Chapter 30. Code parallelization effort of the flux module of the National Combustion Code -- Chapter 31. Parallelization of a chaotic dynamical systems analysis procedure -- Chapter 32. Performance optimization of GeoFEM fluid analysis code on various computer architectures.
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Supercomputers -- Congresses; Computational fluid dynamics; Parallel processing (Electronic computers); Supercomputers; SCIENCE -- Mechanics -- Fluids; Electronic books